Examining Incumbent Performance Accountability in a Single Candidate Local Election: A Case Study of the 2024 Pangkalpinang Local Election - Imron Rosyadi Hamid; Sri Handayani; Dewi Ambarwati; Husnul Hakim; Dafis Ubaidillah Assiddiq; Muhamad Imron; Ariandi A Zulkarnain (Journal of Governance Innovation, 2026)
This study examines incumbent performance accountability in the 2024 single-candidate local election in Pangkalpinang City and its influence on electoral outcomes that culminated in the victory of the blank ballot option. Using a qualitative case study approach, the research draws on in-depth interviews, document analysis, media reports, LP3ES survey data (January 2025), and other secondary sources related to local governance and political dynamics. The findings show that the incumbent administration achieved several notable accomplishments, including a significant increase in regional investment realization from IDR 279.5 billion in 2020 to approximately IDR 4.9 trillion in 2024, urban infrastructure development, the construction of the Kubah Timah Grand Mosque, and improvements in employment and governance indicators. Despite these achievements, citizens continued to face persistent challenges in public services, including inadequate public transportation, waste management problems, limited access to clean water, and concerns regarding bureaucratic performance and local economic conditions. Survey results indicate that the victory of the blank ballot option (44.0%) over the sole candidate (38.6%) was driven primarily by perceptions of inadequate political representation, the absence of meaningful electoral alternatives, and negative evaluations of the candidate’s track record. Furthermore, most respondents reported stagnant or worsening household economic conditions. The study concludes that accountability in single-candidate elections is determined not only by development achievements and administrative performance but also by political representation, government responsiveness, and democratic legitimacy.